Term Rewriting System R:
[x]
f(a, f(a, x)) -> f(c, f(b, x))
f(b, f(b, x)) -> f(a, f(c, x))
f(c, f(c, x)) -> f(b, f(a, x))

Termination of R to be shown.

`   R`
`     ↳Dependency Pair Analysis`

R contains the following Dependency Pairs:

F(a, f(a, x)) -> F(c, f(b, x))
F(a, f(a, x)) -> F(b, x)
F(b, f(b, x)) -> F(a, f(c, x))
F(b, f(b, x)) -> F(c, x)
F(c, f(c, x)) -> F(b, f(a, x))
F(c, f(c, x)) -> F(a, x)

Furthermore, R contains one SCC.

`   R`
`     ↳DPs`
`       →DP Problem 1`
`         ↳Narrowing Transformation`

Dependency Pairs:

F(c, f(c, x)) -> F(a, x)
F(b, f(b, x)) -> F(c, x)
F(a, f(a, x)) -> F(b, x)
F(b, f(b, x)) -> F(a, f(c, x))
F(c, f(c, x)) -> F(b, f(a, x))
F(a, f(a, x)) -> F(c, f(b, x))

Rules:

f(a, f(a, x)) -> f(c, f(b, x))
f(b, f(b, x)) -> f(a, f(c, x))
f(c, f(c, x)) -> f(b, f(a, x))

On this DP problem, a Narrowing SCC transformation can be performed.
As a result of transforming the rule

F(a, f(a, x)) -> F(c, f(b, x))
one new Dependency Pair is created:

F(a, f(a, f(b, x''))) -> F(c, f(a, f(c, x'')))

The transformation is resulting in one new DP problem:

`   R`
`     ↳DPs`
`       →DP Problem 1`
`         ↳Nar`
`           →DP Problem 2`
`             ↳Narrowing Transformation`

Dependency Pairs:

F(b, f(b, x)) -> F(c, x)
F(c, f(c, x)) -> F(b, f(a, x))
F(a, f(a, f(b, x''))) -> F(c, f(a, f(c, x'')))
F(b, f(b, x)) -> F(a, f(c, x))
F(a, f(a, x)) -> F(b, x)
F(c, f(c, x)) -> F(a, x)

Rules:

f(a, f(a, x)) -> f(c, f(b, x))
f(b, f(b, x)) -> f(a, f(c, x))
f(c, f(c, x)) -> f(b, f(a, x))

On this DP problem, a Narrowing SCC transformation can be performed.
As a result of transforming the rule

F(b, f(b, x)) -> F(a, f(c, x))
one new Dependency Pair is created:

F(b, f(b, f(c, x''))) -> F(a, f(b, f(a, x'')))

The transformation is resulting in one new DP problem:

`   R`
`     ↳DPs`
`       →DP Problem 1`
`         ↳Nar`
`           →DP Problem 2`
`             ↳Nar`
`             ...`
`               →DP Problem 3`
`                 ↳Narrowing Transformation`

Dependency Pairs:

F(c, f(c, x)) -> F(a, x)
F(a, f(a, f(b, x''))) -> F(c, f(a, f(c, x'')))
F(a, f(a, x)) -> F(b, x)
F(b, f(b, f(c, x''))) -> F(a, f(b, f(a, x'')))
F(c, f(c, x)) -> F(b, f(a, x))
F(b, f(b, x)) -> F(c, x)

Rules:

f(a, f(a, x)) -> f(c, f(b, x))
f(b, f(b, x)) -> f(a, f(c, x))
f(c, f(c, x)) -> f(b, f(a, x))

On this DP problem, a Narrowing SCC transformation can be performed.
As a result of transforming the rule

F(c, f(c, x)) -> F(b, f(a, x))
one new Dependency Pair is created:

F(c, f(c, f(a, x''))) -> F(b, f(c, f(b, x'')))

The transformation is resulting in one new DP problem:

`   R`
`     ↳DPs`
`       →DP Problem 1`
`         ↳Nar`
`           →DP Problem 2`
`             ↳Nar`
`             ...`
`               →DP Problem 4`
`                 ↳Narrowing Transformation`

Dependency Pairs:

F(a, f(a, f(b, x''))) -> F(c, f(a, f(c, x'')))
F(b, f(b, f(c, x''))) -> F(a, f(b, f(a, x'')))
F(c, f(c, f(a, x''))) -> F(b, f(c, f(b, x'')))
F(b, f(b, x)) -> F(c, x)
F(a, f(a, x)) -> F(b, x)
F(c, f(c, x)) -> F(a, x)

Rules:

f(a, f(a, x)) -> f(c, f(b, x))
f(b, f(b, x)) -> f(a, f(c, x))
f(c, f(c, x)) -> f(b, f(a, x))

On this DP problem, a Narrowing SCC transformation can be performed.
As a result of transforming the rule

F(a, f(a, f(b, x''))) -> F(c, f(a, f(c, x'')))
one new Dependency Pair is created:

F(a, f(a, f(b, f(c, x')))) -> F(c, f(a, f(b, f(a, x'))))

The transformation is resulting in one new DP problem:

`   R`
`     ↳DPs`
`       →DP Problem 1`
`         ↳Nar`
`           →DP Problem 2`
`             ↳Nar`
`             ...`
`               →DP Problem 5`
`                 ↳Narrowing Transformation`

Dependency Pairs:

F(c, f(c, f(a, x''))) -> F(b, f(c, f(b, x'')))
F(a, f(a, f(b, f(c, x')))) -> F(c, f(a, f(b, f(a, x'))))
F(c, f(c, x)) -> F(a, x)
F(b, f(b, x)) -> F(c, x)
F(a, f(a, x)) -> F(b, x)
F(b, f(b, f(c, x''))) -> F(a, f(b, f(a, x'')))

Rules:

f(a, f(a, x)) -> f(c, f(b, x))
f(b, f(b, x)) -> f(a, f(c, x))
f(c, f(c, x)) -> f(b, f(a, x))

On this DP problem, a Narrowing SCC transformation can be performed.
As a result of transforming the rule

F(b, f(b, f(c, x''))) -> F(a, f(b, f(a, x'')))
one new Dependency Pair is created:

F(b, f(b, f(c, f(a, x')))) -> F(a, f(b, f(c, f(b, x'))))

The transformation is resulting in one new DP problem:

`   R`
`     ↳DPs`
`       →DP Problem 1`
`         ↳Nar`
`           →DP Problem 2`
`             ↳Nar`
`             ...`
`               →DP Problem 6`
`                 ↳Narrowing Transformation`

Dependency Pairs:

F(a, f(a, f(b, f(c, x')))) -> F(c, f(a, f(b, f(a, x'))))
F(b, f(b, f(c, f(a, x')))) -> F(a, f(b, f(c, f(b, x'))))
F(a, f(a, x)) -> F(b, x)
F(c, f(c, x)) -> F(a, x)
F(b, f(b, x)) -> F(c, x)
F(c, f(c, f(a, x''))) -> F(b, f(c, f(b, x'')))

Rules:

f(a, f(a, x)) -> f(c, f(b, x))
f(b, f(b, x)) -> f(a, f(c, x))
f(c, f(c, x)) -> f(b, f(a, x))

On this DP problem, a Narrowing SCC transformation can be performed.
As a result of transforming the rule

F(c, f(c, f(a, x''))) -> F(b, f(c, f(b, x'')))
one new Dependency Pair is created:

F(c, f(c, f(a, f(b, x')))) -> F(b, f(c, f(a, f(c, x'))))

The transformation is resulting in one new DP problem:

`   R`
`     ↳DPs`
`       →DP Problem 1`
`         ↳Nar`
`           →DP Problem 2`
`             ↳Nar`
`             ...`
`               →DP Problem 7`
`                 ↳Polynomial Ordering`

Dependency Pairs:

F(b, f(b, f(c, f(a, x')))) -> F(a, f(b, f(c, f(b, x'))))
F(c, f(c, f(a, f(b, x')))) -> F(b, f(c, f(a, f(c, x'))))
F(b, f(b, x)) -> F(c, x)
F(a, f(a, x)) -> F(b, x)
F(c, f(c, x)) -> F(a, x)
F(a, f(a, f(b, f(c, x')))) -> F(c, f(a, f(b, f(a, x'))))

Rules:

f(a, f(a, x)) -> f(c, f(b, x))
f(b, f(b, x)) -> f(a, f(c, x))
f(c, f(c, x)) -> f(b, f(a, x))

The following dependency pairs can be strictly oriented:

F(b, f(b, x)) -> F(c, x)
F(a, f(a, x)) -> F(b, x)
F(c, f(c, x)) -> F(a, x)

Additionally, the following usable rules w.r.t. to the implicit AFS can be oriented:

f(a, f(a, x)) -> f(c, f(b, x))
f(b, f(b, x)) -> f(a, f(c, x))
f(c, f(c, x)) -> f(b, f(a, x))

Used ordering: Polynomial ordering with Polynomial interpretation:
 POL(c) =  0 POL(b) =  0 POL(a) =  0 POL(f(x1, x2)) =  1 + x2 POL(F(x1, x2)) =  x2

resulting in one new DP problem.

`   R`
`     ↳DPs`
`       →DP Problem 1`
`         ↳Nar`
`           →DP Problem 2`
`             ↳Nar`
`             ...`
`               →DP Problem 8`
`                 ↳Narrowing Transformation`

Dependency Pairs:

F(b, f(b, f(c, f(a, x')))) -> F(a, f(b, f(c, f(b, x'))))
F(c, f(c, f(a, f(b, x')))) -> F(b, f(c, f(a, f(c, x'))))
F(a, f(a, f(b, f(c, x')))) -> F(c, f(a, f(b, f(a, x'))))

Rules:

f(a, f(a, x)) -> f(c, f(b, x))
f(b, f(b, x)) -> f(a, f(c, x))
f(c, f(c, x)) -> f(b, f(a, x))

On this DP problem, a Narrowing SCC transformation can be performed.
As a result of transforming the rule

F(a, f(a, f(b, f(c, x')))) -> F(c, f(a, f(b, f(a, x'))))
one new Dependency Pair is created:

F(a, f(a, f(b, f(c, f(a, x''))))) -> F(c, f(a, f(b, f(c, f(b, x'')))))

The transformation is resulting in one new DP problem:

`   R`
`     ↳DPs`
`       →DP Problem 1`
`         ↳Nar`
`           →DP Problem 2`
`             ↳Nar`
`             ...`
`               →DP Problem 9`
`                 ↳Narrowing Transformation`

Dependency Pairs:

F(c, f(c, f(a, f(b, x')))) -> F(b, f(c, f(a, f(c, x'))))
F(a, f(a, f(b, f(c, f(a, x''))))) -> F(c, f(a, f(b, f(c, f(b, x'')))))
F(b, f(b, f(c, f(a, x')))) -> F(a, f(b, f(c, f(b, x'))))

Rules:

f(a, f(a, x)) -> f(c, f(b, x))
f(b, f(b, x)) -> f(a, f(c, x))
f(c, f(c, x)) -> f(b, f(a, x))

On this DP problem, a Narrowing SCC transformation can be performed.
As a result of transforming the rule

F(b, f(b, f(c, f(a, x')))) -> F(a, f(b, f(c, f(b, x'))))
one new Dependency Pair is created:

F(b, f(b, f(c, f(a, f(b, x''))))) -> F(a, f(b, f(c, f(a, f(c, x'')))))

The transformation is resulting in one new DP problem:

`   R`
`     ↳DPs`
`       →DP Problem 1`
`         ↳Nar`
`           →DP Problem 2`
`             ↳Nar`
`             ...`
`               →DP Problem 10`
`                 ↳Narrowing Transformation`

Dependency Pairs:

F(a, f(a, f(b, f(c, f(a, x''))))) -> F(c, f(a, f(b, f(c, f(b, x'')))))
F(b, f(b, f(c, f(a, f(b, x''))))) -> F(a, f(b, f(c, f(a, f(c, x'')))))
F(c, f(c, f(a, f(b, x')))) -> F(b, f(c, f(a, f(c, x'))))

Rules:

f(a, f(a, x)) -> f(c, f(b, x))
f(b, f(b, x)) -> f(a, f(c, x))
f(c, f(c, x)) -> f(b, f(a, x))

On this DP problem, a Narrowing SCC transformation can be performed.
As a result of transforming the rule

F(c, f(c, f(a, f(b, x')))) -> F(b, f(c, f(a, f(c, x'))))
one new Dependency Pair is created:

F(c, f(c, f(a, f(b, f(c, x''))))) -> F(b, f(c, f(a, f(b, f(a, x'')))))

The transformation is resulting in one new DP problem:

`   R`
`     ↳DPs`
`       →DP Problem 1`
`         ↳Nar`
`           →DP Problem 2`
`             ↳Nar`
`             ...`
`               →DP Problem 11`
`                 ↳Narrowing Transformation`

Dependency Pairs:

F(b, f(b, f(c, f(a, f(b, x''))))) -> F(a, f(b, f(c, f(a, f(c, x'')))))
F(c, f(c, f(a, f(b, f(c, x''))))) -> F(b, f(c, f(a, f(b, f(a, x'')))))
F(a, f(a, f(b, f(c, f(a, x''))))) -> F(c, f(a, f(b, f(c, f(b, x'')))))

Rules:

f(a, f(a, x)) -> f(c, f(b, x))
f(b, f(b, x)) -> f(a, f(c, x))
f(c, f(c, x)) -> f(b, f(a, x))

On this DP problem, a Narrowing SCC transformation can be performed.
As a result of transforming the rule

F(a, f(a, f(b, f(c, f(a, x''))))) -> F(c, f(a, f(b, f(c, f(b, x'')))))
one new Dependency Pair is created:

F(a, f(a, f(b, f(c, f(a, f(b, x')))))) -> F(c, f(a, f(b, f(c, f(a, f(c, x'))))))

The transformation is resulting in one new DP problem:

`   R`
`     ↳DPs`
`       →DP Problem 1`
`         ↳Nar`
`           →DP Problem 2`
`             ↳Nar`
`             ...`
`               →DP Problem 12`
`                 ↳Narrowing Transformation`

Dependency Pairs:

F(c, f(c, f(a, f(b, f(c, x''))))) -> F(b, f(c, f(a, f(b, f(a, x'')))))
F(a, f(a, f(b, f(c, f(a, f(b, x')))))) -> F(c, f(a, f(b, f(c, f(a, f(c, x'))))))
F(b, f(b, f(c, f(a, f(b, x''))))) -> F(a, f(b, f(c, f(a, f(c, x'')))))

Rules:

f(a, f(a, x)) -> f(c, f(b, x))
f(b, f(b, x)) -> f(a, f(c, x))
f(c, f(c, x)) -> f(b, f(a, x))

On this DP problem, a Narrowing SCC transformation can be performed.
As a result of transforming the rule

F(b, f(b, f(c, f(a, f(b, x''))))) -> F(a, f(b, f(c, f(a, f(c, x'')))))
one new Dependency Pair is created:

F(b, f(b, f(c, f(a, f(b, f(c, x')))))) -> F(a, f(b, f(c, f(a, f(b, f(a, x'))))))

The transformation is resulting in one new DP problem:

`   R`
`     ↳DPs`
`       →DP Problem 1`
`         ↳Nar`
`           →DP Problem 2`
`             ↳Nar`
`             ...`
`               →DP Problem 13`
`                 ↳Narrowing Transformation`

Dependency Pairs:

F(a, f(a, f(b, f(c, f(a, f(b, x')))))) -> F(c, f(a, f(b, f(c, f(a, f(c, x'))))))
F(b, f(b, f(c, f(a, f(b, f(c, x')))))) -> F(a, f(b, f(c, f(a, f(b, f(a, x'))))))
F(c, f(c, f(a, f(b, f(c, x''))))) -> F(b, f(c, f(a, f(b, f(a, x'')))))

Rules:

f(a, f(a, x)) -> f(c, f(b, x))
f(b, f(b, x)) -> f(a, f(c, x))
f(c, f(c, x)) -> f(b, f(a, x))

On this DP problem, a Narrowing SCC transformation can be performed.
As a result of transforming the rule

F(c, f(c, f(a, f(b, f(c, x''))))) -> F(b, f(c, f(a, f(b, f(a, x'')))))
one new Dependency Pair is created:

F(c, f(c, f(a, f(b, f(c, f(a, x')))))) -> F(b, f(c, f(a, f(b, f(c, f(b, x'))))))

The transformation is resulting in one new DP problem:

`   R`
`     ↳DPs`
`       →DP Problem 1`
`         ↳Nar`
`           →DP Problem 2`
`             ↳Nar`
`             ...`
`               →DP Problem 14`
`                 ↳Narrowing Transformation`

Dependency Pairs:

F(b, f(b, f(c, f(a, f(b, f(c, x')))))) -> F(a, f(b, f(c, f(a, f(b, f(a, x'))))))
F(c, f(c, f(a, f(b, f(c, f(a, x')))))) -> F(b, f(c, f(a, f(b, f(c, f(b, x'))))))
F(a, f(a, f(b, f(c, f(a, f(b, x')))))) -> F(c, f(a, f(b, f(c, f(a, f(c, x'))))))

Rules:

f(a, f(a, x)) -> f(c, f(b, x))
f(b, f(b, x)) -> f(a, f(c, x))
f(c, f(c, x)) -> f(b, f(a, x))

On this DP problem, a Narrowing SCC transformation can be performed.
As a result of transforming the rule

F(a, f(a, f(b, f(c, f(a, f(b, x')))))) -> F(c, f(a, f(b, f(c, f(a, f(c, x'))))))
one new Dependency Pair is created:

F(a, f(a, f(b, f(c, f(a, f(b, f(c, x''))))))) -> F(c, f(a, f(b, f(c, f(a, f(b, f(a, x'')))))))

The transformation is resulting in one new DP problem:

`   R`
`     ↳DPs`
`       →DP Problem 1`
`         ↳Nar`
`           →DP Problem 2`
`             ↳Nar`
`             ...`
`               →DP Problem 15`
`                 ↳Narrowing Transformation`

Dependency Pairs:

F(c, f(c, f(a, f(b, f(c, f(a, x')))))) -> F(b, f(c, f(a, f(b, f(c, f(b, x'))))))
F(a, f(a, f(b, f(c, f(a, f(b, f(c, x''))))))) -> F(c, f(a, f(b, f(c, f(a, f(b, f(a, x'')))))))
F(b, f(b, f(c, f(a, f(b, f(c, x')))))) -> F(a, f(b, f(c, f(a, f(b, f(a, x'))))))

Rules:

f(a, f(a, x)) -> f(c, f(b, x))
f(b, f(b, x)) -> f(a, f(c, x))
f(c, f(c, x)) -> f(b, f(a, x))

On this DP problem, a Narrowing SCC transformation can be performed.
As a result of transforming the rule

F(b, f(b, f(c, f(a, f(b, f(c, x')))))) -> F(a, f(b, f(c, f(a, f(b, f(a, x'))))))
one new Dependency Pair is created:

F(b, f(b, f(c, f(a, f(b, f(c, f(a, x''))))))) -> F(a, f(b, f(c, f(a, f(b, f(c, f(b, x'')))))))

The transformation is resulting in one new DP problem:

`   R`
`     ↳DPs`
`       →DP Problem 1`
`         ↳Nar`
`           →DP Problem 2`
`             ↳Nar`
`             ...`
`               →DP Problem 16`
`                 ↳Narrowing Transformation`

Dependency Pairs:

F(a, f(a, f(b, f(c, f(a, f(b, f(c, x''))))))) -> F(c, f(a, f(b, f(c, f(a, f(b, f(a, x'')))))))
F(b, f(b, f(c, f(a, f(b, f(c, f(a, x''))))))) -> F(a, f(b, f(c, f(a, f(b, f(c, f(b, x'')))))))
F(c, f(c, f(a, f(b, f(c, f(a, x')))))) -> F(b, f(c, f(a, f(b, f(c, f(b, x'))))))

Rules:

f(a, f(a, x)) -> f(c, f(b, x))
f(b, f(b, x)) -> f(a, f(c, x))
f(c, f(c, x)) -> f(b, f(a, x))

On this DP problem, a Narrowing SCC transformation can be performed.
As a result of transforming the rule

F(c, f(c, f(a, f(b, f(c, f(a, x')))))) -> F(b, f(c, f(a, f(b, f(c, f(b, x'))))))
one new Dependency Pair is created:

F(c, f(c, f(a, f(b, f(c, f(a, f(b, x''))))))) -> F(b, f(c, f(a, f(b, f(c, f(a, f(c, x'')))))))

The transformation is resulting in one new DP problem:

`   R`
`     ↳DPs`
`       →DP Problem 1`
`         ↳Nar`
`           →DP Problem 2`
`             ↳Nar`
`             ...`
`               →DP Problem 17`
`                 ↳Remaining Obligation(s)`

The following remains to be proven:
Dependency Pairs:

F(b, f(b, f(c, f(a, f(b, f(c, f(a, x''))))))) -> F(a, f(b, f(c, f(a, f(b, f(c, f(b, x'')))))))
F(c, f(c, f(a, f(b, f(c, f(a, f(b, x''))))))) -> F(b, f(c, f(a, f(b, f(c, f(a, f(c, x'')))))))
F(a, f(a, f(b, f(c, f(a, f(b, f(c, x''))))))) -> F(c, f(a, f(b, f(c, f(a, f(b, f(a, x'')))))))

Rules:

f(a, f(a, x)) -> f(c, f(b, x))
f(b, f(b, x)) -> f(a, f(c, x))
f(c, f(c, x)) -> f(b, f(a, x))

Termination of R could not be shown.
Duration:
0:00 minutes